2013
DOI: 10.1177/0194599813510885
|View full text |Cite
|
Sign up to set email alerts
|

Limited Evidence: Higher Efficacy of Nasal Saline Irrigation over Nasal Saline Spray in Chronic Rhinosinusitis—An Update and Reanalysis of the Evidence Base

Abstract: It should be explained to adult patients with chronic rhinosinusitis that there is limited information on the relative effect of nasal saline irrigation and nasal saline spray on subjective symptom improvement, since there is only 1 trial available with a moderate risk of bias showing limited benefit of irrigation over spray.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Furthermore, these large-volume, low-pressure devices can mediate adverse effects of head position or nasal cavity anatomy on distribution . Saline nasal lavage is low cost and has both high patient acceptance and a high benefit-to-risk margin . Though the evidence regarding large-volume saline irrigation is promising, more high-quality evidence is needed to definitively establish its benefit compared with other forms of treatment such as nasal spray …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these large-volume, low-pressure devices can mediate adverse effects of head position or nasal cavity anatomy on distribution . Saline nasal lavage is low cost and has both high patient acceptance and a high benefit-to-risk margin . Though the evidence regarding large-volume saline irrigation is promising, more high-quality evidence is needed to definitively establish its benefit compared with other forms of treatment such as nasal spray …”
Section: Discussionmentioning
confidence: 99%
“…The authors found that large-volume, low-pressure irrigation devices resulted in better distribution to the nasal cavity and sinuses, especially after surgery, than low-volume devices. Large-volume, low-pressure saline sinus irrigation is a widely recommended treatment for CRS, which is low cost and has a high patient acceptance and benefit-to-risk margin …”
Section: Introductionmentioning
confidence: 99%
“…When nasal polyps are present in CRS, patients should be treated with intranasal therapy, including topical intranasal steroids and/or saline nasal irrigation for symptomatic relief, in addition to long-term management of the nasal polyps themselves with intranasal glucocorticoids which decrease polyp size, polyp recurrence, decrease nasal symptoms, and improve nasal airflow [6, [62][63][64][65][66][67][68][69][70]. Glucocorticoids have been shown to impact epithelial GM-CSF and prolong eosinophil survival [71].…”
Section: Chronic Rhinosinusitis With Nasal Polypsmentioning
confidence: 99%
“…Long-term oral macrolides may be beneficial because of their anti-inflammatory effects, but this needs to be further elucidated through further study of randomized placebo-controlled trials to better assess the benefits versus risks [15, [74][75][76][77]. Intranasal saline irrigation should be used, as opposed to intranasal saline spray because of increased effectiveness on symptom relief and improving quality of life [68,78].…”
Section: Chronic Rhinosinusitis With Nasal Polypsmentioning
confidence: 99%